The Concept of Odious Debt : Some Considerations - Nehru, Vikram; Thomas, Mark (2012)
Despite the popularity of the term among advocates of debt forgiveness, there is little agreement on a workable definition of "odious" debts and there are but few examples where the concept has been invoked in law to justify non-payment of sovereign debts. Most often, these have been cases when a successor state or government has refused to honor certain debts contracted by its predecessor state or government. Repudiating sovereign debts on broader grounds - such as that money may have been misused by the borrower or that results were not as hoped for at the outset of lending - would create real risks not only of reduced financial flows to poorer countries as a result of the danger of ex post challenges to lenders' claims, but also of moral hazard and lack of project ownership. This paper presents a discussion of the extant legal and financial environment facing developing country sovereign borrowers and develops a proposed approach within this environment to address issues of concern underlying the concept of odious or illegitimate debt. The authors make the case for focusing attention on codes of conduct along the lines of the Equator Principles and on refining forward-looking attempts to increase aid effectiveness and recover stolen assets.